2019
DOI: 10.1055/a-0813-4411
|View full text |Cite
|
Sign up to set email alerts
|

Standards Used by a Clinical and Scientific Endometriosis Center for the Diagnosis and Therapy of Patients with Endometriosis

Abstract: Endometriosis is one of the most common benign gynecological diseases. The extremely heterogeneous complex of symptoms complicates the diagnosis and treatment of this disease. In most patients, there is a latency period of several years between the first occurrence of symptoms and the definitive diagnosis. This paper aims (1) to evaluate standards for the diagnosis and treatment of patients with (symptoms suspicious for) endometriosis in terms of feasibility, and (2) to assess the potential use of data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…This means that a survey investigating the quality of results cannot be effectively implemented [18]. A first retrospective analysis showed that a diagnostic and treatment concept based on the main presenting symptom was introduced as a single center concept in a special outpatient clinic for endometriosis and that this made it possible to provide a guideline-based diagnosis and treatment [19]. The aim of the QS ENDO survey is to identify indicators which can be used to measure the quality of treatment.…”
Section: Zusammenfassungmentioning
confidence: 99%
“…This means that a survey investigating the quality of results cannot be effectively implemented [18]. A first retrospective analysis showed that a diagnostic and treatment concept based on the main presenting symptom was introduced as a single center concept in a special outpatient clinic for endometriosis and that this made it possible to provide a guideline-based diagnosis and treatment [19]. The aim of the QS ENDO survey is to identify indicators which can be used to measure the quality of treatment.…”
Section: Zusammenfassungmentioning
confidence: 99%
“…The heterogeneity of endometriosis symptoms delays the diagnosis and makes obtaining a correct diagnosis more difficult [28]. rASRM scores are not correlated with patientsʼ symptoms.…”
Section: Symptommentioning
confidence: 99%
“…Endometriosis is a hormone-related, chronic inflammation in women. Approximately 27 000 women were treated in hospital for endometriosis in Germany in 2016 1 . The prevalence is much higher, however, affecting between 5 and 15% of women of childbearing age 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Im Jahr 2016 wurden in Deutschland ca. 27 000 Patientinnen aufgrund einer Endometriose stationär behandelt 1 . Die Prävalenz liegt deutlich höher und beträgt ca.…”
Section: Introductionunclassified